Effect of Gender and Preoperative Diagnosis on Results of Revision Total Knee Arthroplasty - Pun, Stephanie Y. (Springer-Verlag, 2008)
Recent studies question an effect of gender on outcome of primary TKA. We questioned whether the results of revision TKA were affected by gender. We separated 67 revision TKAs by gender and preoperative diagnosis into four groups (arthrofibrosis, infection, instability, and wear and loosening). Each revision TKA was individually matched by age and gender to two primary TKAs. Postoperative Knee Society pain and function scores after revision TKA were lower than for primary TKA for both females and males. However, postoperative Knee Society pain and function scores were similar in males and females. Postoperative pain and function scores were lower for all revision groups compared with primary TKA, except for pain and function scores after revision for instability. Postoperative pain and function scores were higher for instability and wear or loosening than for arthrofibrosis. Our data suggest the results of revision TKA are affected by preoperative diagnosis but not gender. Level of Evidence: Level III, retrospective matched cohort study. See Guidelines for Authors for a complete description of levels of evidence.